Perturbations in the Photosynthetic Pigment Status Result in Photooxidation-Induced Crosstalk between Carotenoid and Porphyrin Biosynthetic Pathways - Park, Joon-Heum; Tran, Lien H.; Jung, Sunyo (Frontiers in Plant Science, 2017)
Possible crosstalk between the carotenoid and porphyrin biosynthetic pathways under photooxidative conditions was investigated by using their biosynthetic inhibitors, norflurazon (NF) and oxyfluorfen (OF). High levels of protoporphyrin IX (Proto IX) accumulated in rice plants treated with OF, whereas Proto IX decreased in plants treated with NF. Both NF and OF treatments resulted in greater decreases in MgProto IX, MgProto IX methyl ester, and protochlorophyllide. Activities and transcript levels of most porphyrin biosynthetic enzymes, particularly in the Mg-porphyrin branch, were greatly down-regulated in NF and OF plants. In contrast, the transcript levels of GSA, PPO1, and CHLD as well as FC2 and HO2 were upregulated in NF-treated plants, while only moderate increases in FC2 and HO2 were observed in the early stage of OF treatment. Phytoene, antheraxanthin, and zeaxanthin showed high accumulation in NF-treated plants, whereas other carotenoid intermediates greatly decreased. Transcript levels of carotenoid biosynthetic genes, PSY1 and PDS, decreased in response to NF and OF, whereas plants in the later stage of NF treatment exhibited up-regulation of BCH and VDE as well as recovery of PDS. However, perturbed porphyrin biosynthesis by OF did not noticeably influence levels of carotenoid metabolites, regardless of the strong down-regulation of carotenoid biosynthetic genes. Both NF and OF plants appeared to provide enhanced protection against photooxidative damage, not only by scavenging of Mg-porphyrins, but also by up-regulating FC2, HO2, and Fe-chelatase, particularly with increased levels of zeaxanthin via up-regulation of BCH and VDE in NF plants. On the other hand, the up-regulation of GSA, PPO1, and CHLD under inhibition of carotenogenic flux may be derived from the necessity to recover impaired chloroplast biogenesis during photooxidative stress. Our study demonstrates that perturbations in carotenoid and porphyrin biosynthesis coordinate the expression of their biosynthetic genes to sustain plastid function at optimal levels by regulating their metabolic flux in plants under adverse stress conditions.